2020
DOI: 10.3390/ijerph17041183
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Characterization of Extended-Spectrum β-Lactamase- and Carbapenemase-Producing Bacteria from Hospital Sewage, Treated Effluents and Receiving Rivers

Abstract: Hospital sewage plays a key role in the dissemination of antibiotic-resistant genes (ARGs) by serving as an environmental antimicrobial resistance reservoir. In this study, we aimed to characterize the cephalosporin- and carbapenem-resistant isolates from hospital sewage and receiving rivers. The results showed that ESBL (blaCTX-M) and carbapenemase genes (blaNDM and blaKPC) were widely detected in a number of different bacterial species. These resistance genes were mainly harbored in Enterobacteriaceae, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 39 publications
9
34
4
1
Order By: Relevance
“…As that effluent does not receive any disinfecting pretreatment, this may contribute to the dissemination of MDR bacteria that were also found in the sanitary effluent located near the Complexo Hospital de Clínicas (Universidade Federal do Paraná) (CHC-UFPR). Our results are consistent with previous studies, showing that MDR Aeromonas strains are spreading rapidly in different environmental compartments and may be involved in the maintenance and dissemination of carbapenemase genes (14,18,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As that effluent does not receive any disinfecting pretreatment, this may contribute to the dissemination of MDR bacteria that were also found in the sanitary effluent located near the Complexo Hospital de Clínicas (Universidade Federal do Paraná) (CHC-UFPR). Our results are consistent with previous studies, showing that MDR Aeromonas strains are spreading rapidly in different environmental compartments and may be involved in the maintenance and dissemination of carbapenemase genes (14,18,(29)(30)(31).…”
Section: Discussionsupporting
confidence: 93%
“…Growing levels of drug resistance, especially to β-lactam, have been reported in Aeromonas spp. not only in clinical isolates, but also in isolates from water ecosystems and aquatic organisms (13,29,31). In our study, CTX-M β-lactamase harboring strains were the prevalent group in WWTP that receives high amounts of microbial contaminants from hospitals effluents and other sources as well as in DRW.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…2019; Zhang et al . 2020), rare β‐lactamase‐encoding genes identified in our study deserve further attention. In particular, bla GES‐1 and bla GES‐7 encode ESBLs, whereas bla GES‐5 and bla GES‐16 encode enzymes able to hydrolyse carbapenems (Cuzon et al .…”
Section: Discussionmentioning
confidence: 71%
“…Some of the selected ARB are Acinetobacter baumannii , carbapenem-resistant; Pseudomonas aeruginosa , carbapenem-resistant; Enterobacteriaceae , carbapenem-resistant, 3 rd generation cephalosporin-resistant (with priority 1) and Enterococcus faecium , vancomycin-resistant (with priority 2). Many investigations have been carried out in recent years (( 43 ), ( 44 ), ( 45 ), ( 18 ), ( 46 )) demonstrating the increasing efforts made by research groups in this field and the increasing amount of data collected on their occurrence. The cited investigations concluded that the resistance to antibiotics is generally higher in HWW rather than in domestic wastewater, and if hospital effluent is not properly disinfected it may strongly contribute to the spread of ARB in the environment.…”
Section: Threats and Challenges In Hospital Effluent Management And Tmentioning
confidence: 99%